Emerging themes in international management of human resources - Benson, Philip G. (Research in organizational analysis., 2011)
Emerging Themes in International Management of Human Resources is the third volume in the Research in Organizational Analysis series. This volume investigates important human resource management (HRM) issues within an international context. The papers in this volume provide insight into several HRM areas. First, the international context's effects on management knowledge transfer; privatization of traditionally governmental services; and the relation between social capital and organizational diversity is considered. The second part of this volume is concerned with the issue of staffing in international organizations with special emphasis on HRM selection and termination practices for the cross-national company. Third, women's issues in the international firm are explored. Gender issues such as flexible work arrangements and the role of culturally defined gender egalitarian values on role differences among women and men managers are investigated. Finally, the volume explores the issues of expatriation and repatriation among firms. The role of psychological contracts in supporting successful expatriate experiences; how repatriate support practices influence repatriate organizational commitment; turnover intentions; and career success; and an investigation of repatriation as sense making process are discussed. This volume provides a good basis for understanding how HRM practices are affected by cross-cultural differences and provides insight into best HRM practices for the international organization.